Religiosity and Consumer Ethics - Vitell, Scott J. (Journal of business ethics, 2005)
This article presents the results of an exploratory study that investigated the role that religiosity plays in determining consumer attitudes/beliefs in various situations regarding questionable consumer practices. Two dimensions of religiosity – intrinsic and extrinsic religiousness – were studied. Results indicated that an intrinsic religiousness was a significant determinant of consumer ethical beliefs, but extrinsic religiousness was not related to those beliefs.